Upaya Meningkatkan Aktivitas dan Hasil Belajar Matematika Melalui Model Pembelajaran Problem Posing - Desmulyani (Indra institute Research & Publication, 2022)
The purpose of this study, first, is to explain the increase in students' mathematics learning activities, second, to find out the increase in students' mathematics learning outcomes, after the learning process uses a post solution posing problem posing model.This research is located at MAN 2 Padang City Jalan Gajah Mada no. 100 North Padang District. The subjects of this study were 36 students of class XI IPS 3 for the academic year 2019/2020, consisting of 12 males and 24 females. This research is a Classroom Action Research (CAR), which has two cycles, each of which consists of two meetings. The results of this study, first, for learning activities there was an increase from meeting 1 to meeting 2 in cycle I as well as in cycle II, there was an increase for each activity observed, second, students' mathematics learning outcomes in cycle I, the average value the average is 65, completed 12 people with classical completeness 33.33% and in the second cycle obtained learning outcomes with an average value of 77.94 and completed 23 people with classical completeness 64%. In conclusion, the post-solution posing type of problem posing learning model can increase the activity and learning outcomes of students in class XI IPS 3 MAN 2, Padang City.